Biochemical and Molecular Studies of Active and Passive Defense Systems in Musa Acuminata L. Cv. ‘Jari Buaya’ - Way, Chiang Poh (2006)
Fusarium wilt incidence constitutes one of the major constraints in the development of sustainable banana industry in the country. To date, a cost-effective measure of control for this disease is still not available and farmers are still depending heavily on the use of chemicals to minimize the problem. The use of resistant cultivar to enhance resistant to critical diseases and the reduction of chemicals usage holds the key to surge a better profit margin in the industry. The approach employed in this study was to enhance disease resistant of some of the existing banana cultivars in Malaysia by using biotechnology technique. The objectives of this study were isolation of genes related to plant defense system by using PCR, and analyses of resistant gene candidates (RGCs) in specific host-pathogen interaction, by using reverse transcription-polymerase chain reaction (RT-PCR). Five out of six of the putative diseases RGCs were differentially expressed in the ‘Jari Buaya’ (JB)- Fusarium oxysporum cubense race 4 (Focr4) interactions. RGC1 was induced and involved in this interaction. In addition, the expression of RGC1 was not affected water stress. The transcripts level of RGC2 and RGC3 decreased as the infection progressed from 1 hour to 3 hours. The mentioned three different RGCs belong to the class of nucleotide binding site-leucine rich repeat (NBS-LRR) disease related proteins. Southern hybridization analyses depicted that these genes belonged to a small gene family. The other three RGCs, RGC4, RGC5 and RGC6 were classified in the kinase family. RGC4 and RGC5 were constitutively expressed in JB-Focr4 interaction and no expression was observed for RGC6. This is the first report of globally renowned Focr4 resistant of local banana crop ‘Jari Buaya’ at molecular level in plant active defense system. The accumulation of phenolic compounds and often lignin in plant tissues especially the cell wall and vascular system, is an established plant response to fungal attack. This response has been hypothesized to play an important role in determining passive resistant. Focr4 resistant cultivar, ‘Jari Buaya’ possessed higher amount of phenolic compounds for both the intracellular and cell wall. However, the susceptible cultivar, ‘Rastali’ secreted more phenolics than the resistant cultivar into the environment. The results were in tandem with the phenylalanine ammonia lyase (PAL) enzyme activity. Lignin staining of banana roots unveiled that the resistant cultivar possessed higher PAL activity and more lignin deposition in the roots than the susceptible cultivar.